Analisis Penerapan Owned Media pada PT. Jogja Eco Wisata - Firman Unggul Prayudha; Mohammad Irhas Effendi; Heru Tri Sutiono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2024)
PT Jogja Eco Tourism is a tourism company operating in Yogyakarta, Indonesia. They have a number of media owned assets, such as the official website, social media accounts. This research is Field Reseach. There are eleven (11) problems that lie behind the lack of confidentiality to owned media owned by PT. Jogja Eco Tourism due to lack of management in its managerial terms such as, a) Content Planning, b) Content Building, c) SEO optimization, d) Website Management, e) Social Media Management, f) Quality Control, g) Performance Analysis, h) Interaction with Audiences, i) Integration with Marketing Strategy and also j) Compliance with Law and Ethics as well as k) Lack of human resources. A number of steps have been attempted by PT. Jogja Eco Tourism to solve eleven (11) problems on owned media. There are 6 steps that have been taken by P. jogja Eco tourism in solving these problems. The method is to: (a) set goals (b) posting consistency (c) target audiences (d) management or maintenance (e) content selection up to (f) recruitment of new employees to advance online marketing performance. The settlement has not covered legal and ethical compliance issues, considering that P.T. Jogja Eco Tourism Centre is dealing with the law at the moment.